SIL1 deficiency causes degenerative changes of peripheral nerves and neuromuscular junctions in fish, mice and human - Phan, Vietxuan; Rudolf, Rüdiger; Straka, Tatjana (Neurobiology of disease, 2019)
Background - Marinesco-Sjögren Syndrome (MSS) is a rare neuromuscular condition caused by recessive mutations in the SIL1 gene resulting in the absence of functional SIL1 protein, a co-chaperone for the major ER chaperone, BiP. As BiP is decisive for proper protein processing, loss of SIL1 results in the accumulation of misshaped proteins. This accumulation likely damages and destroys cells in vulnerable tissues, leading to congenital cataracts, cerebellar ataxia, vacuolar myopathy and other MSS phenotypes. Whether the peripheral nervous system (PNS) is affected in MSS has not been conclusively shown. - Methods - To study PNS vulnerability in MSS, intramuscular nerves fibres from MSS patients and from SIL1-deficient mice (woozy) as well as sciatic nerves and neuromuscular junctions (NMJ) from these mice have been investigated via transmission electron microscopic and immunofluorescence studies accompanied by transcript studies and unbiased proteomic profiling. In addition, PNS and NMJ integrity were analyzed via immunofluorescence studies in an MSS-zebrafish model which has been generated for that purpose. - Results - Electron microscopy revealed morphological changes indicative of impaired autophagy and mitochondrial maintenance in distal axons and in Schwann cells. Moreover, changes of the morphology of NMJs as well as of transcripts encoding proteins important for NMJ function were detected in woozy mice. These findings were in line with a grossly abnormal structure of NMJs in SIL1-deficient zebrafish embryos. Proteome profiling of sciatic nerve specimens from woozy mice revealed altered levels of proteins implicated in neuronal maintenance suggesting the activation of compensatory mechanisms. - Conclusion - Taken together, our combined data expand the spectrum of tissues affected by SIL1-loss and suggest that impaired neuromuscular transmission might be part of MSS pathophysiology.
Available online 20 November 2018
Gesehen am 06.08.2019